A semi-automated quantitative comparison of metal artifact reduction in photon-counting computed tomography by energy-selective thresholding - Do, Thuy; Sawall, Stefan; Heinze, Sarah; Reiner, Tobias; Ziener, Christian H.; Stiller, Wolfram; Schlemmer, Heinz-Peter; Kachelrieß, Marc; Kauczor, Hans-Ulrich; Skornitzke, Stephan (Scientific reports, 2020)
An evaluation of energy thresholding and acquisition mode for metal artifact reduction in Photon-counting detector CT (PCD-CT) compared to conventional energy-integrating detector CT (EID-CT) was performed. Images of a hip prosthesis phantom placed in a water bath were acquired on a scanner with PCD-CT and EID-CT (tube potentials: 100, 120 and 140 kVp) and energy thresholds (above 55-75 keV) in Macro and Chess mode. Only high-energy threshold images (HTI) were used. Metal artifacts were quantified by a semi-automated segmentation algorithm, calculating artifact volumes, means and standard deviations of CT numbers. Images of a human cadaver with hip prosthesis were acquired on the PCD-CT in Macro mode as proof-of-concept. Images at 140 kVp showed less metal artifacts than 120 kVp or 100 kVp. HTI (70, 75 keV) had fewer artifacts than low energy thresholds (55, 60, 65 keV). Fewer artifacts were observed in the Macro-HTI (8.9-13.3%) for cortical bone compared to Chess-HTI (9.4-19.1%) and EID-CT (10.7-19.0%) whereas in bone marrow Chess-HTI (19.9-45.1%) showed less artifacts compared to Macro-HTI (21.9-38.3%) and EID-CT (36.4-54.9%). Noise for PCD-CT (56-81 HU) was higher than EID-CT (33-36 HU) irrespective of tube potential. High-energy thresholding could be used for metal artifact reduction in PCD-CT, but further investigation of acquisition modes depending on target structure is required.